Biostratigraphy and taxonomy of Drumian ( Middle Cambrian) agnostid trilobites of the Manuels river formation, Avalonian Newfoundland, Canada - Hildenbrand, Anne; Austermann, Gregor; Ifrim, Christina; Bengtson, Peter (Papers in palaeontology, 2021)
New, accurately located and well-preserved agnostid trilobite material has been collected from the type locality of the Drumian (middle Cambrian, Miaolingian) Manuels River Formation, Newfoundland, Canada. The wellexposed grey to black shales containing the fauna were deposited on the former microcontinent Avalonia. Four interval zones for the succession are proposed, namely, the Tomagnostus fissus, Hypagnostus parvifrons, Ptychagnostus atavus and Ptychagnostus punctuosus zones. The Tomagnostus fissus and Ptychagnostus atavus zones are distinct from each other, which leads to a significantly shorter and stratigraphically higher Ptychagnostus atavus Zone compared with other sections (Scandinavia, South China, Utah and Nevada, Greenland). Specimens of Ptychagnostus atavus, however, occur abundantly, with 107 specimens identified in a short interval of the succession. The Ptychagnostus punctuosus Zone can be correlated globally. The faunal assemblage is comparable to that of Scandinavia, Greenland and England. Ptychagnostus affinis is recorded for the first time from Avalonia. The 1408 collected specimens were assigned to the suborders Agnostina and Eodiscina and to the families Peronopsidae and Ptychagnostidae, and Condylopygidae and Eodiscidae, respectively, with the following species: Peronopsis fallax (Linnarsson), Peronopsis scutalis (Hicks), Hypagnostus parvifrons (Linnarsson), Ptychagnostus punctuosus (Angelin), Ptychagnostus affinis (Brogger), Ptychagnostus atavus (Tullberg), Tomagnostus fissus (Lundgren), Tomagnostus perrugatus (Gr_onwall), Pleuroctenium granulatum (Barrande) and Eodiscus punctatus (Salter).